2020
DOI: 10.1002/ijc.33390
|View full text |Cite
|
Sign up to set email alerts
|

GSDME and its role in cancer: From behind the scenes to the front of the stage

Abstract: Gasdermin E (GSDME), a gene originally involved in hereditary hearing loss, has been associated with several types of cancer in the last two decades. Recently, GSDME was identified as a pore-forming molecule, which is activated following caspase-3-mediated cleavage resulting in so-called secondary necrosis following apoptotic cell death, or in primary necrotic cell death without an apoptotic phase, so-called pyroptosis-like. This implication in cell death execution suggests its potential role as a tumor suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 83 publications
(321 reference statements)
0
51
0
Order By: Relevance
“…The levels of c-myc protein were decreased to undetectable level after TPL treatment for 24 h. This powerful inhibitory effect is a comprehensive result from simultaneously repression protein stability and transcription of c-myc by TPL. GSDME is frequently silenced in human cancers due to hyper-methylation of promoter DNA [59], making cancer cells lack of GSDME are resistant to pyroptosis. It remains a challenge to kill cancers within dysfunction of cell death machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of c-myc protein were decreased to undetectable level after TPL treatment for 24 h. This powerful inhibitory effect is a comprehensive result from simultaneously repression protein stability and transcription of c-myc by TPL. GSDME is frequently silenced in human cancers due to hyper-methylation of promoter DNA [59], making cancer cells lack of GSDME are resistant to pyroptosis. It remains a challenge to kill cancers within dysfunction of cell death machinery.…”
Section: Discussionmentioning
confidence: 99%
“…GSDME mutation was first identified to cause an autosomal dominant hearing impairment. 18 , 174 , 175 GSDME is mostly expressed in the cochlea, placenta, brain, female reproductive tract (especially the placenta), kidney, heart, and muscle. 36 In contrast to non‐tumoral tissues, expression of GSDME is limited in most cancers including gastric cancer, melanoma, CRC, invasive breast cancer, and other human cancers.…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…GSDME , also known as DFNA5 , is located on human chromosome 7p15.3, while Gsdme , also known as Dfna5 , is found on mouse chromosome 6B2.3. GSDME mutation was first identified to cause an autosomal dominant hearing impairment 18,174,175 . GSDME is mostly expressed in the cochlea, placenta, brain, female reproductive tract (especially the placenta), kidney, heart, and muscle 36 .…”
Section: The Mechanism Of the Pyroptosis Pathwaymentioning
confidence: 99%
“…On the other hand, data on GSDME expression levels between cancer and normal samples are controversial: while the majority of translational studies have found downregulated levels of GDME in cancer compared to normal tissue, others have not found such differences. Even more puzzling, there was no clear correlation between GSDME methylation and GSDME expression levels in a number of studies ( 40 ). Overall, however, GSDME appears to represent a potent tumor suppressor gene ( 20 ).…”
Section: Introductionmentioning
confidence: 99%